2014
DOI: 10.1007/s40596-014-0070-6
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Prevalence of the Experience of Death of a Patient by Suicide Among Medical Students and Residents? A Systematic Review

Abstract: Although the data are limited, psychiatry residents commonly experience the death of a patient by suicide. There is a paucity of data on this topic concerning the experiences of medical students and of residents in other specialties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…The prevalence of patient death by suicide across studies ranged from 31 to 69 %. In a new study reported in this collection by Deringer and Caligor [7], 8 of 23 psychiatry resident participants or 35 % had encountered patient suicide at the low end of the range identified by Puttagunta et al [6]. No prevalence data on this experience among medical students and residents in other specialties exist, to our knowledge, and we hope that future empirical work will ascertain the frequency and help define the influence of the experience of patient suicide on physicians-in-training.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…The prevalence of patient death by suicide across studies ranged from 31 to 69 %. In a new study reported in this collection by Deringer and Caligor [7], 8 of 23 psychiatry resident participants or 35 % had encountered patient suicide at the low end of the range identified by Puttagunta et al [6]. No prevalence data on this experience among medical students and residents in other specialties exist, to our knowledge, and we hope that future empirical work will ascertain the frequency and help define the influence of the experience of patient suicide on physicians-in-training.…”
mentioning
confidence: 84%
“…The systematic review of Puttagunta et al [6] highlights the observation that psychiatry residents commonly experience the death of a patient by suicide. The prevalence of patient death by suicide across studies ranged from 31 to 69 %.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to one systematically conducted review [17], the prevalence of psychiatry residents' experience of the death of a patient by suicide ranged from 31 to 69%. Notably, only one of the eight cross-sectional studies included in this review was conducted in the USA, and this study had low numbers of psychiatrists and is now dated [18].…”
Section: Death Of a Patient By Suicidementioning
confidence: 99%
“…While much has been written about the general stresses of residency (e.g., fatigue and sleep disruption, frustrations from working with uncooperative or demanding patients, demoralization from feeling that efforts are not resulting in substantial patient improvements), psychiatry training has its own relatively unique set of stressors, including adversities associated with aggressive acts by patients towards residents and the suicide of a patient [11,15,16]. Loss of patients is a grave stressor for residents in many fields, but loss by suicide carries unique challenges for the physician [1,15].…”
Section: Impact Of Psychiatric Illness During Residency Trainingmentioning
confidence: 99%